Dilemmas with Disciplinary Hierarchies and Ideals of Scientific Research in the Study of Religion - Peedu, Indrek (Implicit Religion, 2023)
While strictly conceptual matters have dominated much of the discussion concerning religion as an object of scientific research, different understandings of the scientific character of the study of religion have also always had a significant role in the scholarly self-understanding. Here two significant conceptualizations of this scientific character—that of the so-called new scientificity (as advocated mostly by scholars from the cognitive science of religion) as well as that of the comparative history of religion—are described in detail and then thoroughly analyzed and criticized. It will be shown how both conceptualizations face problems, but those of the new scientificity are significantly more serious. Lastly, some more general reflections will be offered concerning the significance of these matters for the study of religion overall.